Photonic Activation Function Using Sound Waves - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
We experimentally demonstrate an in-fiber optoacoustic nonlinear activation function based on stimulated Brillouin scattering. The activation function can be tuned all-optically and shows an input-output behaviour of a LeakyReLU, Sigmoid, and quadratic function. Our scheme is coherent and frequency selective, which is suitable for operation in multi-frequency neural networks. In addition, the optoacoustic activation function can amplify its input signal, allowing to compensate on-the-fly for optical losses during propagation.
CRIS-Team Scopus Importer:2023-12-15
Keywords: neuromorphic computing; nonlinear optics; Optical neural networks; stimulated Brillouin scattering